The Influence of Religiosity, Trust, Knowledge and Location on People Interest in Saving at Bank Syariah Indonesia Sub-Branch Office Bengkalis - Azizatul Aulia; M. Alkadri Perdana (Politeknik Negeri Bengkalis, 2022)
This study aims to determine the influence of religiosity, trust, knowledge and location on people interest in saving at Bank Syariah Indonesia Sub-Branch Office Bengkalis. The number of samples in this study was 100 respondents by distributing questionnaires to people who saved at Bank Syariah Indonesia Sub-Branch Office Bengkalis. The research method used is a quantitative approach using a non-probability sampling method with purposive sampling and the analysis method is multiple linear regression. The results of this study indicate that partially religiosity, trust, knowledge and location variables have a significant influence on people interest in saving at Bank Syariah Indonesia Sub-Branch Office Bengkalis. Simultaneously, the variables of religiosity, trust, knowledge, and location have a significant influence on people interest in saving at Bank Syariah Indonesia Sub-Branch Office Bengkalis. The coefficient of determination of religiosity, trust, knowledge and location is 66.1% of the interest in saving.Keywords: Religiosity, Trust, Knowledge and Location